HIF-1α and Nrf2 regulates hypoxia induced overexpression of DDAH1 through promoter activation in prostate cancer. (June 2022) - Parveen, Sakkarai Mohamed Asha; Natani, Sirisha; Sruthi K.K.,; Khilar, Priyanka; Ummanni, Ramesh
Abstract: Dimethylarginine dimethylaminohydrolase-1 ( DDAH1 ) is overexpressed in prostate cancer (PCa) and promotes PCa progression in in vivo through the ADMA-NO pathway by degrading nitric oxide synthase (NOS) inhibitors such as asymmetric dimethylarginine (ADMA) and monomethylamine arginine (L -NMMA). In this study, we investigated the molecular mechanism involved in the overexpression of DDAH1 in PCa and examined its potential role as a therapeutic target. We observed that DDAH1expression is elevated in PCa (PC3, LNCaP, and DU145) cell lines under hypoxia. ChIP and reporter assay results confirmed that DDAH1 expression is positively regulated by HIF-1α through directly binding to the hypoxia response elements (HRE) located within the promoter region between − 1242/− 1238 upstream of its transcription start site (TSS). Under hypoxia, HIF-1α is translocated into the nucleus and activates its target gene expression in PC3 cells. Interestingly, in the event of HIF-1α inhibition or siRNA-mediated knockdown, an alternative transcription factor Nrf2 promotes DDAH1 expression through antioxidant response elements (AREs) on its promoter. ChIP assay results showed that Nrf2 binds to AREs located between –1016 / −1008 bp from the TSS of DDAH1. Furthermore, knockdown of PCa therapeutic target HSP90, an essential co-factor for both HIF-1α and Nrf2 causes attenuation of hypoxia induced DDAH1 overexpression in PCa cells. These results demonstrate that hypoxia induced upregulation of DDAH1 expression is positively regulated by HIF-1α and Nrf2 in association with HSP90. Therefore, targeting tumor angiogenesis promoting DDAH1 along with standard androgen receptor (AR) targeted therapy may offer an effective strategy to prevent PCa progression. Highlights: Dimethylarginine dimethylaminohydrolase-1 ( DDAH1 ) is elevated under hypoxia in PCa (PC3, LNCaP and DU145) cell lines. Transcriptional activation of HIF-1α under hypoxia positively regulates overexpression of DDAH1 via promoter activation. In the event of HIF-1α inactivation an alternative transcription factor Nrf2 is upregulated and promotes DDAH1 expression. HIF-1α and Nrf2 promotes DDAH1 expression through HREs and AREs respectively on its promoter. Hypoxia induces DDAH1 overexpression through HIF-1α / Nrf2 in association with HSP90 in PCa.